Exploring patterns: how to teach when the signals seem to be missing? - Pereyra, Alicia Pérez de; Espinosa, Beatriz Aguilar de; Tossi, Cecilia (The ESPecialist, 2011)
This paper presents the sequence of activities prepared to guide undergraduate students of ESP courses of the Schools of Agricultural Sciences of the Argentine National Universities of Córdoba, Catamarca and Villa María in the recognition of the Problem-Solution pattern in scientific texts of the agricultural domain. The ultimate goal is to find the best possible techniques to help non-native students of English and researchers discover the pattern in an attempt to add a new perspective to reading specialized text, i.e. a clause-relational perspective. Further research in this area will be carried out in the next three years.